Parthenolide regulates microglial and astrocyte function in primary cultures from ALS mice and has neuroprotective effects on primary motor neurons - Nadine Thau-Habermann; Thomas Gschwendtberger; Colin Bodemer; Susanne Petri (PLoS ONE, 2025)
Over the last twenty years, the role of microgliosis and astrocytosis in the pathophysiology of neurodegenerative diseases has increasingly been recognized. Dysregulation of microglial and astrocyte properties and function has been described also in the fatal degenerative motor neuron disease amyotrophic lateral sclerosis (ALS). Microglia cells, the immune cells of the nervous system, can either have an immunonegative neurotoxic or immunopositive neuroprotective phenotype. The feverfew plant (Tanacetum parthenium) derived compound parthenolide has been found to be capable of interfering with microglial phenotype and properties. Positive treatment effects were shown in animal models of neurodegenerative diseases like Alzheimer’s disease and Parkinson’s disease. Now we were able to show that PTL has a modulating effect on primary mouse microglia cells, both wild type and SOD1, causing them to adopt a more neuroprotective potential. Furthermore, we were able to show that PTL, through its positive effect on microglia, also has an indirect positive impact on motor neurons, although PTL itself has no direct effect on these primary motor neurons. The results of our study give reason to consider PTL as a drug candidate for ALS.